User Satisfaction Analysis of Streaming Applications Using the Technology Acceptance Model - David Kalwi Manullang; Yohanes A. R Langi; Dodisutarma Lapihu; Mahardika I. Takaendengan; Eric Alfonsius; Edwin Tenda (J-INTECH ( Journal of Information and Technology), 2026)
The rise of information and communication technology has led to the development of several digital platforms, especially in the entertainment industry, such as community-driven streaming apps. One of the growing platforms is Bstation, which provides anime, comics, and game content. However, in its implementation, several issues are still encountered, such as difficulties in finding content due to irrelevant search results, limited content availability and delayed episode updates, as well as suboptimal viewing experiences, including streaming interruptions and audio-video desynchronization. These problems have an impact on decreasing user comfort, usage frequency, and users’ intention to continue using the application. This investigation assesses Bstation application satisfaction levels through Technology Acceptance Model (TAM) application. Employing quantitative questionnaire methodology, study tests key variables: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Using (ATU), Behavioral Intention (BI), and Actual Use (AU). Although BI and AU correlations appear insignificant, integrated variables clearly impact ATU. Data confirms perceived benefits and ease drive user satisfaction, overshadowing actual usage pattern.